Netherton syndrome plus atopic dermatitis: Two new genetic mutations in the same patient - Agata Moar (Wiley, 2021)
Abstract A child who comes to our attention for the appearance of erythematous, scaly lesions localized to the upper and lower limbs for 2 months. Histological features suggested ichthyosiform disease and concomitant mutations in the SPINK5 and FLG2 genes confirmed Netherton syndrome with severe atopic manifestations.